B-emission Stars in Southern Sky Observed in Bosscha Observatory: Spectroscopic Study of HÎ± Spectral Line Variability - Aprilia Aprilia; Hakim Luthfi Malasan; Geavani Eva Ramadhania; Agus Triono Puri Jatmiko; Mochamad Irfan; Dhimaz Gilang Ramadhan; Ade Nur Istiqomah; Evan Irawan Akbar (Journal of Mathematical and Fundamental Sciences, 2019)
HÎ± line variations of 8 B-emission (Be) stars are presented. Stars that are listed in the Bright Star Catalogue were observed in 2009 at the Bosscha Observatory, Lembang, Indonesia. It was found that 4 stars showed phase changing from Be double-peaked to Be single-peaked emission line profiles, 1 showed single-peaked to double-peaked profiles, 1 showed double-peaked to B-normal, while two other stars did not show phase changing. The stars also showed variations in the V/R and E/C values, which represent the strength of the emission lines. The phase changes were detected from a comparison of the observed data to the current data in the BeSS database.